Improving Elementary Students' Understanding of LCM and GCF Through a Traditional Dakon Game - I Nyoman Bagus Pramartha Pramartha; Komang Hari Santhi Dewi (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Low student ability in determining the Least Common Multiple (LCM) and Greatest Common Factor (GCF) of a number is caused by a lack of student motivation in learning. Nowadays, a learning innovation based on local wisdom is highly needed, one that is not only fun but also educates students according to their needs in the academic field. One local wisdom that can be developed is the Dakon/Congklak game. This research was also conducted to assess the validity, practicality, and effectiveness of traditional Dakon game-based media based on assessments from design experts, media experts, and learning practitioners. The research sample consisted of 40 fourth-grade students with LCM and GCF material. The method used was R&D (Research and Development) with a 4-D development model, namely define, design, development, and disseminate. The methods used to collect data in this research were questionnaires and interviews so that the data obtained would be more accurate and the resulting media would be more useful for users in the future. The results of the learning design expert review showed that the LCM and GCF learning media was categorized as very feasible (94%), the results of the learning media expert review showed that the LCM and GCF learning media was categorized as feasible (82%), the results of individual trials of the LCM and GCF learning media were categorized as very practical (92%), the results of small group trials of the LCM and GCF learning media were categorized as very practical (93%), and the results of field trials of the LCM and GCF learning media were categorized as very practical (97%). Meanwhile, the effectiveness of the development of the developed LCM and GCF learning media effectively improved LCM and GCF learning outcomes based on the results of the Wilcoxon Signed Ranks Test analysis which indicated that the median pre-test rank (Mdn = 5.00) was significantly different from the median post-test rank (Mdn = 9.00), Z = 5.540, p = 0.000. This means that it is known that Sig. 0.000 < 0.05 so there is a significant difference between the pre-test and post-test. Keywords: mathematics, LCM, GCF, dakon, traditional games.